(untitled) (Praxis Educativa, 2026)
The results of a research on various elements that shaped the identity of teachers in basic and higher education in recent years are presented. The study was qualitative, through documentary analysis, based on 61 texts published between 2018 and 2024, in English and Spanish; the documents were obtained from Science Direct and Google Scholar and refer to experiences in 30 countries. The findings indicate that in recent years and at both educational levels there is a global concern about the decrease in teachers’ job stability, their intellectual independence and the psychological and professional discomfort that the work environment causes them from the time they enter until they retire from the teaching profession. In addition, it was found that there is a lack of better policy strategies for the training, professionalization and consensual evaluation of teachers.